PEMIMPIN MUDA YANG BERINTEGRITAS MENURUT 1TIMOTIUS 4:12 RELEVANSINYA TERHADAP ALUMNI STT BIBLIKA JAKARTA - Johanes Witoro (STT BIBLIKA JAKARTA, 2020)
Young leaders in the era of globalization, it can happen in all walks of life, from academia, government, companies and others. but it also needs to be realized that, challenges also exist for young leaders. The challenges are age, then their responsibilities, knowledge, skills and spiritual life, and other things, exemplary factors in speech, behavior, and sanctity of life. A qualitative method approach to young leaders as Alumni of STT Biblika Jakarta from the results of the study, it was found that young leaders, had very good knowledge and understanding of science and 70% expressed leadership skills, but 30% they seemed hesitant in implementing and for exemplary living, in theory are very understanding but seem hesitant in maintaining exemplary living. It can be concluded that young leaders need a balance between the knowledge and practice of their leaders in order to become young leaders with integrity.